2012
DOI: 10.1007/s11277-012-0557-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cubic Permutation Polynomials for Turbo Codes

Abstract: Quadratic permutation polynomials (QPPs) have been widely studied and used as interleavers in turbo codes. However, less attention has been given to cubic permutation polynomials (CPPs). This paper proves a theorem which states sufficient and necessary conditions for a cubic permutation polynomial to be a null permutation polynomial. The result is used to reduce the search complexity of CPP interleavers for short lengths (multiples of 8, between 40 and 352), by improving the distance spectrum over the set of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…In [2,7,8] few methods for finding good QPP or CPP based interleavers are given. These methods also take into account other parameters of QPP/CPP based interleavers (such as D parameter or spread and refined nonlinearity degree).…”
Section: Comparison Between Dithered Lpps and Good Qpps Or Cpps From mentioning
confidence: 99%
See 4 more Smart Citations
“…In [2,7,8] few methods for finding good QPP or CPP based interleavers are given. These methods also take into account other parameters of QPP/CPP based interleavers (such as D parameter or spread and refined nonlinearity degree).…”
Section: Comparison Between Dithered Lpps and Good Qpps Or Cpps From mentioning
confidence: 99%
“…These methods also take into account other parameters of QPP/CPP based interleavers (such as D parameter or spread and refined nonlinearity degree). In Tables 6 and 7, the our dithered LPPs are compared with the QPPs from [2] or [7,8] and the CPPs from [2], for some lengths, considering the simulated FER and the minimum distance. It is observed that for all reported lengths dithered LPPs lead to higher or equal minimum distances (excepting CPP of length 40 and QPPs of lengths 320, 560, 848 and 1008, respectively).…”
Section: Comparison Between Dithered Lpps and Good Qpps Or Cpps From mentioning
confidence: 99%
See 3 more Smart Citations